Informal Care and the Great Recession - Joan Costa-Font; Martin Karlsson; Henning Øien (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2015)
Macroeconomic downturns can have an important impact on the availability of informal and formal long-term care. This paper investigates how the market for informal care changed during and after the Great Recession in Europe. We use data from the Survey of Health, Aging and Retirement in Europe, which includes a rich set of variables covering waves before and after the Great Recession. We find evidence of an increase in the availability of informal care and a reduction in the use of formal health services (doctor visits and hospital stays) after the economic downturn when controlling for year and country fixed effects. This trend is mainly driven by changes in care provision of individuals not cohabiting with the care recipient. We also find a small negative association between old-age health and crisis severity. The results are robust to the inclusion of individual characteristics, individual-specific effects and regionspecific time trends.
Keywords: J1; I18; 330; long-term care; informal care; great recession; downturn; old age dependency